Asian Values Discourses and Its Impact on Freedom of Expression in Social Media - Syahwal; Raihan Muhammad (Universitas Negeri Semarang, 2025)
This study originates from the discourse on social media regarding a set of Asian cultural values that often conflict with universal human rights principles. These values, recognized in human rights studies as Asian values, are seen in various studies as intertwined with threats to human rights. Therefore, this study aims to uncover the forms of discourse surrounding Asian values on social media and their potential impact on freedom of expression. Based on these issues, this research employs a non-doctrinal method, which examines law within various extra-legal contexts, to explore the discourse of Asian values emerging on social media—especially on the 'X' platform—and its relationship with political and religious expression on social media. The study reveals that the tendency of Asian values to support authoritarianism also extends to social media. Various expressions are then labeled as uncivil and contrary to Indonesian culture. This situation leads Asian values to act as a trigger for the shrinking of civil space on social media.